Hubungan Kebutuhan Spiritual Dengan Kualitas Hidup Lansia Di Desa Tanjung Anom Tahun 2023: Relationship between Spiritual Needs and the Quality of Life of the Elderly at Tanjung Anom Village 2023 - Siallagan, Sarnita (Jurnal Keperawatan Muhammadiyah, 2024)
The purpose of this research is to identify spiritual requirements and how they relate to the quality of life of the elderly in Tanjung Anom Village. A cross-sectional design was used in the investigation. We used a purposive sample strategy to choose 78 persons to be our respondents. In order to be included in the sample, individuals must be 60 years old or older, have proof of residency in Tanjung Anom village, and have good communication and social skills. The chi-square test was used to analyze the data, and the results showed that 56.4% of the elderly had their spiritual needs met, 65.4% had good life quality, and there was a significant relationship between the two in Tanjung Anom village in 2023 (P.value= 0.001). In 2023, the elderly in Tanjung Anom village may be said to have a correlation between their spiritual demands and their quality of life.